Utilization of Information and Communication Technology in the Management of Secondary Schools in Iwajowa Local Government Area of Oyo State, Nigeria (Kwasu International Journal of Educational Management and Leadership, 2026)
The integration of Information and Communication Technology (ICT) in educational management has enhanced school administration and learning outcomes worldwide. However, in rural areas like Iwajowa Local Government, Oyo State, ICT adoption in secondary schools remains limited and underexplored. This study investigates the utilization of Information and Communication Technology in the management of secondary schools in Iwajowa local government area of Oyo State, Nigeria.The study employed a descriptive survey design. The population of the study comprised of 236 administrators and teachers in all the 9 public secondary schools in the local government area. A total of 200 secondary school administrators and teachers (87 male, 113 female) respondents were selected using stratified random sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics to analyze demographic information of the respondents, Pearson’s correlation, regression analysis, and ANOVA to analyze the research questions and the research hypotheses at 0.05 level of significance. Findings revealed that ICT is highly utilized for student record management, staff communication, and lesson planning (Mean = 3.00), a low level of ICT adoption, primarily due to poor infrastructure (3.01), lack of training (2.49), and inadequate funding (2.98). However, the correlation coefficient (r = 0.018) suggests a weak and non-significant relationship between ICT utilization and school management and this may be attributed to the unequal access to ICT resources in rural schools, which limits its potential impact. The study recommended, among others, that government should increase investment in ICT infrastructure, targeted teacher training programs, and provision of digital resources to enhance school management in rural areas.